Multilevel Determinants of Mental Health: A Systematic Review of Access, Stigma, and Social Inequities - Indi Dwi Shofi Yanti; Marian Muse Osman (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
Mental health outcomes are increasingly understood as the result of interacting structural, cultural, and individual-level influences that shape patterns of care access, service engagement, and recovery trajectories. This study synthesizes evidence from systematic reviews to examine how key domains including accessibility and equity, cultural sensitivity, stigma and mental health literacy, therapeutic communication, and social determinants collectively influence mental health systems and outcomes. The findings indicate that barriers to care extend beyond service availability, encompassing affordability constraints, institutional limitations, and disparities affecting marginalized populations. Cultural context further mediates how mental health conditions are perceived and managed, influencing both help-seeking behavior and treatment adherence. Stigma remains a critical cross-cutting issue, contributing to delays in accessing care and negatively affecting treatment engagement and quality of life . In parallel, broader social conditions such as socioeconomic disadvantage and social isolation play a significant role in shaping vulnerability and resilience. Taken together, the evidence highlights the importance of adopting a comprehensive perspective that integrates health system improvements with culturally informed and socially responsive approaches to mental health care.